PENATALAKSANAAN FISIOTERAPI PADA KASUS CEREBRAL PALSY SPASTIC QUADRIPLEGI DENGAN MENGGUNAKAN NEURO DEVELOPMENT TREATMENT DI RSUD CIKALONG WETAN KABUPATEN BANDUNG BARAT - Dimas Gilang Kurniawan; Ika Rahman (Journal of Health Science and Physiotherapy, 2021)
Cerebral Palsy is a heterogeneous group of clinical syndromes that describe permanent disturbances of movement and posture. Characterized by abnormalities of muscle tone, posture, and movement that limits the patient's activity. To determine the management of physiotherapy in reducing muscle spasticity and increasing motor skills in patients with Cerebral Palsy Spastic Quadrilegi with Neuro Development Treatment. After doing physiotherapy six times, result of the spastic assessment decrease in the hip abductor muscle group from T1: 2 to T6: 0, the adductor from T1: 1 to T6: 0, the hip flexor T1: 3 to T6: 0, the knee flexor T1: 4 became T6: 0, dorsal flexion of ankle T1: 3 to T6: 0. Then there is no improvement in motor skills. It can be conclusion that the administration of NDT (Neuro Development Treatment) given 6 times only reduces muscle spasticity in Cerebral Palsy patients